Alternative approach to the preparation of chitosan beads - (:unkn) unknown (ELSEVIER SCIENCE BV, 1998)
A controlled-release protein delivery system was investigated by using bovine serum albumin (BSA) as a model drug. Chitosan was reacted with sodium alginate in the presence of tripolyphosphate for bead formation. Spherical beads were produced with diameter in the range 0.78-0.92 mm and 13-90% encapsulation efficiency. It appeared that encapsulation of BSA was affected by the initial protein and sodium alginate concentrations and the presence of pectin (1%) in the external phase. Bead sizes changed with alginate concentration and pectin addition. Release properties of the beads were affected by their BSA content. Addition of pectin to the external phase decreased the percentage release of BSA from the beads. It can be concluded that alginate-reinforced chitosan beads might be a potential delivery system for protein encapsulation. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: alginate; beads; bovine serum albumin; chitosan; controlled-release; drug delivery systems; pectin; CONTROLLED-RELEASE; ALGINATE MICROCAPSULES